Breastfeeding Knowledge and Practices among Mothers of Children under 2 Years of Age Living in a Military Barrack in Southwest Nigeria - Modupe Rebekah Akinyinka, MBBS, MPH, FMCPH; Foluke Adenike Olatona, MBBS, MPH, FMCPH; Esther Oluwakemi Oluwole, MBBS, MPH, FMCPH (Global Health and Education Projects, Inc., 2016)
Background: Human milk is uniquely superior as a source of nutrition for infants, and breastfeeding has many benefi ts. This study determined the breastfeeding knowledge and practices of women who have children aged 0-2 years living in a Naval Barracks. Methods: This descriptive cross sectional study was carried out among 220 women in a Naval Barracks selected using systematic random sampling method. Pre tested questionnaires were administered by trained interviewers, and data was analyzed using Epi info 2000 and Statistical Package for Social Sciences version 19. Results: There was generally fair knowledge about breastfeeding among the women. Most of the respondents (97.3%) had ever breastfed their babies, 56.5% of them initiated breastfeeding within an hour of delivery, 24.1% admitted that they gave pre lacteal feeds, 74.1% practiced exclusive breastfeeding for a mean period of 4.98 months and 30.7% engaged in bottle-feeding. Several factors were signifi cantly associated with breastfeeding practices. Conclusions: Breastfeeding practices varied among the respondents despite the fair knowledge. Global Health Implications: This study reveals the need to educate women and communities worldwide particularly in low-income countries about good breastfeeding practices. Targeting these women will help to improve maternal and child health. Key words: Breastfeeding Practices • Military Barracks • Breastfeeding Knowledge • Nigeria Copyright © 2015 Akinyinka et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.